2008
DOI: 10.1162/pres.17.5.512
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Visual and Auditory Feedback in Virtual Obstacle Walking

Abstract: This paper describes evaluation experiments for visual and auditory feedback in a virtual obstacle walking scenario. Two studies with healthy subjects were carried out using the actuated gait orthosis LOKOMAT. Controlled factors for the visual feedback experiment were three different perspectives and 2D/3D vision. In the auditory feedback experiment, controlled factors were rhythmic distance feedback and gradual foot clearance feedback. For the visual and auditory feedback experiments, outcome was assessed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…Evidence from previous studies suggest that external auditory timing signals improve temporal stride symmetry and gait variability in healthy subjects and stroke patients [22,23]. Continuous auditory feedback improves the performance in obstacle avoidance task [28]. This implies that at least some amount of adaptation in our study was due to the auditory cues; however, it was the goal of this study to establish a quantitative comparison of visual and haptic modalities, rather than establishing the absolute measures and benchmarks of task-specific adaptation.…”
Section: Discussionmentioning
confidence: 95%
“…Evidence from previous studies suggest that external auditory timing signals improve temporal stride symmetry and gait variability in healthy subjects and stroke patients [22,23]. Continuous auditory feedback improves the performance in obstacle avoidance task [28]. This implies that at least some amount of adaptation in our study was due to the auditory cues; however, it was the goal of this study to establish a quantitative comparison of visual and haptic modalities, rather than establishing the absolute measures and benchmarks of task-specific adaptation.…”
Section: Discussionmentioning
confidence: 95%
“…A recent study on motor adaptation [22] seems to confirm these findings: healthy subjects who were given rhythmic auditory cues while walking on a treadmill showed greater gait modifications after training than did people who received both auditory and visual cues. Similarly, a study on the Lokomat [24], [65] showed that healthy subjects receiving auditory feedback and visual feedback (VR environment) increased their gait speed more than subjects receiving visual feedback only, but did not show greater improvements in other performance metrics. Treadmill stepping while following a prescribed walking pattern with the help of visual feedback, a condition that has been referred to as precision or attentive walking, has been shown to significantly increase the motor and cognitive demands of treadmill walking on healthy subjects [66], [67] since it requires them to control and constantly monitor their foot placement.…”
Section: Discussionmentioning
confidence: 96%
“…We rendered the obstacles invisible, so as to minimize any possible influence of visual feedback on their discrimination responses [15]. This allowed us to more accurately assess the influence of our haptic cue feedback.…”
Section: Methodsmentioning
confidence: 99%